Analisis kapal perikanan pelaku illegal fishing yang ditangani Pangkalan Pengawasan Sumberdaya Kelautan dan Perikanan Bitung - Amiruddin Amiruddin; Patrice Nelson Isaak Kalangi; Vivanda O. J. Modaso (Universitas Sam Ratulangi, 2022)
Illegal fishing is a fishing activity that does not comply with laws and regulations. The practice of illegal fishing does not only have a negative impact on the sustainability of resources, but also has a negative impact on the community, regional and national economy. The Bitung Marine and Fisheries Resources Surveillance Base (Pangkalan PSDKP Bitung) has the task of surveilancing and enforcing laws and regulations in the marine and fisheries sector in Sulawesi waters. The objectives of this research were: 1) to identify the areas prone to illegal fishing in the State Fisheries Management Area of the Republic of Indonesia (WPPNRI), 2) to examine the characteristics of illegal fishing perpetrator related to the specifications of the ship and its origin. All data related to the purpose of this study were obtained from the Bitung PSDKP Base. The data was then analyzed using descriptive statistics in the form of simple tables, graphs and proportion values. The results of this study indicate that there are three areas prone to illegal fishing, in order, namely: 1) the territorial sea and the ZEEI of the Sulawesi Sea in the western waters of the Sitaro Islands Regency and Sangihe Islands Regency, 2) the northern waters of the Talaud Islands Regency, and 3) theÂ Maluku Sea east of Minahasa. Based on the characteristics of the vessels, 71.1% of the vessels were from the Philippines, captained by Filipinos, and manned by Filipino crew. Ships ofÂ£5 GT in capacityaccount for 68.8%, and 87.3% of ships are made of wood. Around 60.7% of ships are equipped with three kinds of radio and navigation equipment. The fishing gear operated is mainly (78.6 %)tuna handline.Illegal fishingatau penangkapan ikan secara tidak sah adalah aktivitas penangkapan ikan yang tidak sesuai dengan peraturan dan perundang-undangan yang berlaku. Praktik illegal fishing tidak hanya berdampak buruk pada kondisi sumberdaya, tetapi juga berdampak buruk pada perekonomian masyarakat, daerah, dan nasional. Pangkalan Pengawasan Sumberdaya Kelautan dan Perikanan (PSDKP) Bitung mempunyai tugas mengawasi dan menegakkan peraturan dan perundang-undangan di bidang kelautan dan perikanan di wilayah perairan Sulawesi. Penelitian ini telah dilakukan dengan tujuan untuk: 1) Mengetahui sebaran daerah rawan terjadinya illegalfishingdi Wilayah Pengelolaan Perikanan Negara Republik Indonesia (WPPNRI), 2) Mengetahui karakteristik pelaku illegalfishingberkaitan dengan spesifikasi kapal dan asalnya. Semua data yang berkaitan dengan tujuan penelitian ini diperoleh dari Pangkalan PSDKP Bitung. Data tersebut kemudian dianalisis menggunakan statistika deskriptif dalam bentuk tabel-tabel sederhana, grafik dan nilai proporsi. Hasil penelitian ini menunjukkan bahwa ada tiga daerah rawan tindakan illegalfishing, secara berurut yakni: 1)Laut teritorial dan ZEEI Laut Sulawesi di perairan sebelah barat Kabupaten Kepulauan Sitaro dan Kabupaten Kepulauan Sangihe, 2)Perairan sebelah utara Kabupaten Kepulauan Talaud, dan 3) Perairan Laut Maluku sebelah timur Minahasa. Berdasarkan karakteristik kapal, 71.1 % kapal yang tertangkap berasal dari Filipina, dinakhodai oleh warga Filipina, dan diawaki oleh ABK Filipina. Kapal berukuran Â£5 GT mencapai 68.8 %, dan 87.3 % terbuat dari bahan kayu. Sekitar 60.7% kapal dilengkapi dengan tiga macam alat radio dan navigasi. Alat tangkap yang dioperasikan didominasi oleh pancing ulur vertikal untuk tuna (78.6 %).